Principal Leadership Management Strategies in Developing Teacher Professionalism - Zaeni, Lutfy Muhamad; Wasliman, Iim (Papanda Publisher, 2025)
Teacher professionalism remains a critical challenge in educational systems globally, with many educators failing to meet established professional standards despite various certification programs. This study examined principal management practices in developing teacher professionalism, addressing the gap between management theory and educational leadership practice in professional development initiatives. A qualitative descriptive study was conducted at two Indonesian elementary schools (SDN Mekarjaya 2 and SDN Panyusuhan 1) over six months. Data were collected through semi-structured interviews with 24 participants, participant observations during professional development activities, and document analysis of school policies and evaluation reports. G.R. Terry's management framework served as the theoretical lens for analyzing planning, organizing, implementing, and evaluating functions in teacher professional development. The findings revealed systematic implementation of four integrated management functions. Planning encompassed comprehensive needs assessment (100% implementation), resource allocation (90%), and strategic objective setting. Organizing established clear team structures with defined roles and collaborative approaches involving senior teachers. Implementation featured structured delivery through hands-on workshops, community of practice methodologies, and interactive learning sessions. Evaluation employed four-tiered assessment measuring participant satisfaction, competency improvement (28% average increase in theoretical understanding), behavioral change through classroom observation, and long-term educational impact. Key obstacles included initial resistance to change, technology integration challenges, and resource constraints, addressed through preparatory seminars, mentoring systems, and innovative resource-sharing solutions. The study demonstrates how systematic management approaches complement traditional leadership paradigms in developing teacher professionalism. The integration of management functions with communities of practice principles creates supportive environments that enhance teacher commitment, professional identity development, and sustained behavioral change. These findings contribute to educational leadership literature by providing empirical evidence of specific management practices that effectively transform teacher professionalism within contextually situated learning environments.